2010
DOI: 10.1089/ten.tec.2010.0016
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Quantitative Micro-Computed Tomography Evaluation of Angiogenesis in an Axially Vascularized Tissue-Engineered Bone Construct

Abstract: In this study quantitative analysis of vascularization using micro-CT along with 3D reconstruction and automatic analysis exhibit to be a powerful method superior to histological evaluation of cross sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 46 publications
1
62
0
1
Order By: Relevance
“…17 Moreover, recent studies have demonstrated axially vascularization of different bone scaffolds such as custom-made processed bovine cancellous bone matrix, particulated porous hydroxyapatite, and beta-tricalcium phosphate matrix using the AVL model. 14,15 It is known that the venous and the graft segments of the AVL are responsible for early angiogenesis up to day 14. 25 The thick tunica media of the artery was thought to avoid vascular sprouting at early stages after AVL construction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Moreover, recent studies have demonstrated axially vascularization of different bone scaffolds such as custom-made processed bovine cancellous bone matrix, particulated porous hydroxyapatite, and beta-tricalcium phosphate matrix using the AVL model. 14,15 It is known that the venous and the graft segments of the AVL are responsible for early angiogenesis up to day 14. 25 The thick tunica media of the artery was thought to avoid vascular sprouting at early stages after AVL construction.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies using a particulated porous hydroxyapatite and beta-tricalcium phosphate matrix, a predominance of neocapillaries arising from the venous part of the AVL was found at 2 weeks, whereas no further difference was detected at the 4-week explantation time point between the arterial and venous AVL segments. 15 We determined the vascular network both histologically and by microcomputed tomography. Histology can evaluate a limited number of 2D cross sections and therefore yields a 2D approximation, while mCT offers the opportunity to reconstruct and morphometrically evaluate the vascular network of the entire specimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study evaluated the vascular ingrowth within a gel system consisting of an arteriovenous loop placed in a particulated porous hydroxyapatite and btricalcium phosphate matrix with and without incorporation of exogenous growth factors. 25 Micro-CT analysis was performed with Microfil contrast enhancement to visualize the 3D geometry of the vascular tree within the construct (Fig. 3B), allowing for easy and accurate quantification compared to 2D histological analysis.…”
mentioning
confidence: 99%